2021
DOI: 10.1111/mec.16198
|View full text |Cite
|
Sign up to set email alerts
|

The genomic basis of army ant chemosensory adaptations

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 133 publications
(222 reference statements)
0
5
0
Order By: Relevance
“…The expansion of the 9-exon OR subfamily is a common phenomenon in the Hymenoptera. For example, a large number of 9-exon OR subfamily members were found in the genome of the army ant Eciton burchellii, despite having a reduced gene complement relative to other ants [ 39 ]. The 9-exon OR subfamily was also large in the paper wasp, accounting for almost half of the Polistes ORs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of the 9-exon OR subfamily is a common phenomenon in the Hymenoptera. For example, a large number of 9-exon OR subfamily members were found in the genome of the army ant Eciton burchellii, despite having a reduced gene complement relative to other ants [ 39 ]. The 9-exon OR subfamily was also large in the paper wasp, accounting for almost half of the Polistes ORs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research also found that pheromones regulate ant reproductive behavior. Volatile pheromones secreted by newborn larvae stimulate the production of oxytocin in the adult ants' brains, which in turn leads to their nurturing behavior towards the larvae [7,8].…”
Section: Swarm Intelligencementioning
confidence: 99%
“…These ants thus have the potential to offer new insights into the relationship between social organization, diet, brain size, and mosaic structure. Army ants (Subfamily Dorylinae) are mass-foraging generalist or specialist predators that may form huge colonies of morphologically and behaviorally specialized workers (Kronauer, 2020;McKenzie et al, 2021). Predatory poneroid ants hunt alone or in groups and differ in diet and social complexity (Peeters, 1997;Ward, 2014;Hanisch et al, 2020).…”
Section: Predatory Ants As Models Of Brain Evolutionmentioning
confidence: 99%
“…These differences in hunting and prey-capture strategies, as well as the involvement of different sensory modalities in prey localization (Masuko, 1990;Gronenberg and Tautz, 1994;De la Mora et al, 2008), are associated with changes in behavioral demands for prey recognition, foraging communication, and foraging-task specialization (Schmidt and Overal, 2009) that will be reflected in volumetric changes in functionally specialized brain compartments. Other socioecological traits (activity pattern, nesting and foraging habits, foraging range, and prey distribution) are associated with morphological adaptations such as eye and antenna size, and sensilla type and density, and in turn linked with prey selection, diet, and brain mosaicism (Menzi, 1987;Polidori et al, 2012;Narendra et al, 2013;Ramirez-Esquivel et al, 2014;Bulova et al, 2016;Wittwer et al, 2017;Heinze et al, 2018;McKenzie et al, 2021). Prey olfactory detection and discrimination likely depend on the diversity of sensillae and receptors, and their neuronal projections into individual antennal lobe glomeruli that vary in size and number (Couto et al, 2005;van der Woude and Smid, 2016).…”
Section: Predatory Ants As Models Of Brain Evolutionmentioning
confidence: 99%